If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10 + 2a = 2(4a + 2) Reorder the terms: 10 + 2a = 2(2 + 4a) 10 + 2a = (2 * 2 + 4a * 2) 10 + 2a = (4 + 8a) Solving 10 + 2a = 4 + 8a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-8a' to each side of the equation. 10 + 2a + -8a = 4 + 8a + -8a Combine like terms: 2a + -8a = -6a 10 + -6a = 4 + 8a + -8a Combine like terms: 8a + -8a = 0 10 + -6a = 4 + 0 10 + -6a = 4 Add '-10' to each side of the equation. 10 + -10 + -6a = 4 + -10 Combine like terms: 10 + -10 = 0 0 + -6a = 4 + -10 -6a = 4 + -10 Combine like terms: 4 + -10 = -6 -6a = -6 Divide each side by '-6'. a = 1 Simplifying a = 1
| 20=-10y+4(-10y+15) | | 2(2x-7)=46 | | 2-6(y+1)=4(2-3y)+6 | | t(-16t+8)=0 | | 2(2.2b-1.6+b)=6.4 | | 5(1+8w)=10w+25 | | 8b+8=2(8p+4) | | -4y+8(4y+11)=36 | | 3(5x-4)=7x-12 | | 5/6×=-20 | | 3y-4=9y+32 | | 7v/4=49 | | q^2+1.4q-0.51=0 | | 52-x^2+10x=10 | | -9x+8x-5+2+2x= | | 102.5=2L+2W-11.75 | | 8t(-2t)=0 | | -4+8(4y+11)=36 | | -14x+18-11-2x+3= | | 3+2(1+5n)=65 | | 7.2(x-3.75)=-28.8 | | 6x-44*4x=22 | | 8x-2x+4=8 | | 5+2.50g=2.75 | | 12+48x+36y=528 | | 2x+2(0.25x)=5 | | 6v+3(-2v+5)=69 | | 6x-44*4x= | | 8-3x+7x-23= | | 3x+4.2=2q | | 13/4=x/12 | | 28x-35y=10 |